The Effect of Mix Design on Mechanical and Thermal Properties Oil Palm Shell (OPS) Lightweight Concrete - Fahrizal Zulkarnain S.T., M.Sc., Ph.D; Mohd. Zailan Suleiman; Eravan Serri (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
This paper discusses the use of oil palm shell (OPS) as lightweight aggregate in lightweight concrete especially in the structure application has been proven by previous researches. As industrial waste material, OPS can be the alternative material to be used in the construction industry. With its advantage as heat resistant of OPS. A total of 15 mix design with 3 different cement/sand ratio (1.7, 1.8, 1.9) and 5 cement content in mix design (300, 350, 400, 450, 500 kg/m3) has been tested. The result showed mechanical and thermal properties for all mix.